Impact of marketing strategy on the competitiveness of tourism and hotel businesses - Samonova, Tatiana; Antonenko, Irina; Melnyk, Iryna; Parubets, Oleh; Kuchai, Oksana (My University, 2022)
The relevance of the study is conditioned by the need to analyse modern marketing theory and its provisions and systematise current methods of marketing promotion of travel companies. In this regard, the purpose of the study is to develop an algorithm for creating a marketing strategy for a tourist and hotel business enterprise, describe the process of identifying competitors, disclose parameters for assessing the competitiveness of tourist and hotel business enterprises, systematise strategies for increasing demand during periods of low demand for tourist services, list elements of a modern marketing strategy for the development of tourist and hotel business enterprises, present the main characteristics of brand positioning in the market. The main approach in the study is the method of system analysis, which was used to consider a complex system of relationships between marketing strategy and the effectiveness of the tourism business. In addition, the following methods of scientific knowledge were used: synthesis, deduction, classification, data grouping, comparison, generalisation, and analysis of information sources. The study presents the results of the analysis, developed an algorithm for creating a marketing strategy for a tourist and hotel business enterprise, described the process of identifying competitors, identified the parameters for assessing the competitiveness of tourist and hotel business enterprises, systematised strategies for increasing demand during periods of low demand for tourist services, listed elements of a modern marketing strategy for the development of tourist and hotel business enterprises, presents the main characteristics of brand positioning in the market. Актуальність дослідження зумовлена ​​необхідністю аналізу сучасної теорії маркетингу та її положень та систематизації сучасних методів маркетингового просування туристичних компаній. У зв’язку з цим метою дослідження є розробка алгоритму формування маркетингової стратегії підприємства туристично-готельного бізнесу, опис процесу ідентифікації конкурентів, розкриття параметрів оцінки конкурентоспроможності підприємств туристично-готельного бізнесу, систематизація стратегій підвищення попиту в періоди низького попиту на туристичні послуги, перелік елементів сучасної маркетингової стратегії розвитку підприємства туристично-готельного бізнесу, представлення основних характеристик позиціонування бренду на ринку. Основним підходом у дослідженні є метод системного аналізу, який використано для розгляду складної системи взаємозв’язків між маркетинговою стратегією та ефективністю туристичного бізнесу. Крім того, використовувалися такі методи наукового пізнання: синтез, дедукція, класифікація, групування даних, порівняння, узагальнення, аналіз джерел інформації. У дослідженні наведено результати аналізу, розроблено алгоритм створення маркетингової стратегії підприємства туристично-готельного бізнесу, описано процес виявлення конкурентів, визначено параметри оцінки конкурентоспроможності підприємств туристично-готельного бізнесу, систематизовано стратегії підвищення попиту в періоди низького попиту на туристичні послуги, перераховано елементи сучасної маркетингової стратегії розвитку підприємства туристично-готельного бізнесу, наведено основні характеристики позиціонування бренду на ринку.
Keywords: image of the tourist brand; price competitiveness; sustainable development of the tourism industry; диверсифікація туристичного ринку; диверсифікація туристичного ринку; економіка; імідж туристичного бренду; цінова конкурентоспроможність; сталий розвиток туристичної галузі; сталий розвиток туристичної галузі; ‎кафедра туристичного та готельного бізнесу‎